2008 12th International Software Product Line Conference 2008
DOI: 10.1109/splc.2008.32
|View full text |Cite
|
Sign up to set email alerts
|

Visual Tool Support for Configuring and Understanding Software Product Lines

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 20 publications
0
31
0
2
Order By: Relevance
“…For instance, making a decision might cause several features to become selected, which in turn require a number of components to be implemented. The details of this meta-model are out of scope for this paper and the interested reader is guided to a previous publication [19] for further information.…”
Section: Meta-modelmentioning
confidence: 99%
“…For instance, making a decision might cause several features to become selected, which in turn require a number of components to be implemented. The details of this meta-model are out of scope for this paper and the interested reader is guided to a previous publication [19] for further information.…”
Section: Meta-modelmentioning
confidence: 99%
“…Many SPL research approaches (Czarnecki et al, 2004) focus on single development artefacts. In order to exploit real benefits of a product line we need to connect these isolated models (Botterweck et al, 2008). The authors have identified potential PD tasks in a form of scenarios.…”
Section: Product Derivation Tasksmentioning
confidence: 99%
“…The authors have identified potential PD tasks in a form of scenarios. The scenarios are illustrated with a sample product line (RESCU product line (Botterweck et al, 2008)). Decision, Feature and Component models are modeled artefacts from the RESCU product line for automotive restraint systems.…”
Section: Product Derivation Tasksmentioning
confidence: 99%
“…Feature models are information models that describe a set of possible products presented in a single coherent model [3], [4]. Because of the increased demand for software products, variability models tend to grow very large in size (comprising thousands of features in several cases) and increase in complexity due to the myriad of relationships that could exist among the features in the model, making it a challenge and error-prone to handle, manage and visualise these large-scale models using current existing approaches [5], [6], [7], [8]. However, in a real-life context, feature relationships can emerge in a number of ways.…”
Section: Introductionmentioning
confidence: 99%